Manipulating intermediates at the Au-Ti0₂ interface over InP nanopillar array for photoelectrochemical CO₂ reduction - Liu, Guanyu (2022)
Photoelectrochemical (PEC) reduction of CO2 with H2O is a promising approach to convert solar energy and greenhouse gas into value-added chemicals or fuels. However, the exact role of structures and interfaces of photoelectrodes in governing the photoelectrocatalytic processes in terms of both activity and selectivity remains elusive. Herein, by systematically investigating the InP photocathodes with Au-TiO2 interfaces, we discover that nanostructuring of InP can not only enhance the photoresponse owing to increased light absorption and prolonged minority carrier lifetime, but also improve selectivity toward CO production by providing more abundant interfacial contact points between Au and TiO2 than planar photocathodes. In addition, theoretical studies on the Au-TiO2 interface demonstrate that the charge transfer between Au and TiO2, which is locally confined to the interface, strengthens the binding of the CO∗ intermediate on positively charged Au interfacial sites, thus improving CO2 photoelectroreduction to form CO. An optimal Au-TiO2/InP nanopillar-array photocathode exhibits an onset potential of +0.3 V vs reversible hydrogen electrode (RHE) and a Faradaic efficiency of 84.2% for CO production at -0.11 V vs RHE under simulated AM 1.5G illumination at 1 sun. The present findings of the synergistic effects of the structure and interface on the photoresponse and selectivity of a photoelectrode provide insights into the development of III-V semiconductor-based PEC systems for solar fuel generation.